The Causal Role of Magnesium Deficiency in the Neuroinflammation, Pain Hypersensitivity and Memory/Emotional Deficits in Ovariectomized and Aged Female Mice - Zhang J; Mai CL; Xiong Y; Lin ZJ; Jie YT; Mai JZ; Liu C; Xie MX; Zhou X; Liu XG (Dove Medical Press, 2021)
Jun Zhang,1- 3,* Chun-Lin Mai,1,* Ying Xiong,1 Zhen-Jia Lin,1 Ying-Tao Jie,1 Jie-Zhen Mai,1 Chong Liu,1 Man-Xiu Xie,4 Xin Zhou,2,3 Xian-Guo Liu1,5,6 1Department of Physiology and Pain Research Center, Zhongshan School of Medicine, Sun Yat-sen University, Guangzhou, 510080, People's Republic of China; 2Department of Anesthesiology, Guangdong Provincial People's Hospital, Guangdong Academy of Medical Sciences, Guangzhou, 510080, People's Republic of China; 3Guangdong Cardiovascular Institute, Guangzhou, 510080, People's Republic of China; 4Department of Anesthesiology, Sun Yat-sen University Cancer Center, State Key Laboratory of Oncology in South China, Collaborative Innovation Center for Cancer Medicine, Guangzhou, 510060, People's Republic of China; 5Department of Anesthesiology, Guangdong Second Provincial Central Hospital, Guangzhou, 510317, People's Republic of China; 6Guangdong Province Key Laboratory of Brain Function and Disease, Guangzhou, 510080, People's Republic of China*These authors contributed equally to this workCorrespondence: Xian-Guo Liu; Xin Zhou Email liuxg@mail.sysu.edu.cn; zhoux89@mail2.sysu.edu.cnPurpose: Postmenopausal women often suffer from chronic pain, memory decline and mood depression. The mechanisms underlying the neuronal disorders are not fully understood, and effective treatment is still lacking.Methods: Oral administration of magnesium-L-threonate was tested to treat the neuronal disorders in ovariectomized and aged female mice. The pain hypersensitivity, memory function and depression-like behaviors were measured with a set of behavioral tests. Western blots, immunochemistry and in situ hybridization were used to assess molecular changes.Results: Chronic oral administration of magnesium-L-threonate substantially prevented or reversed the chronic pain and memory/emotional deficits in both ovariectomized and aged female mice. We found that phospho-p65, an active form of nuclear factor-kappaB, tumor necrosis factor-alpha and interleukin-1 beta were significantly upregulated in the neurons of dorsal root ganglion, spinal dorsal horn and hippocampus in ovariectomized and aged mice. The microglia and astrocytes were activated in spinal dorsal horn and hippocampus. Calcitonin gene-related peptide, a marker for peptidergic C-fibers, was upregulated in dorsal horn, which is associated with potentiation of C-fiber-mediated synaptic transmission in the model mice. In parallel with neuroinflammation and synaptic potentiation, free Mg2+ levels in plasma, cerebrospinal fluid and in dorsal root ganglion neurons were significantly reduced. Oral magnesium-L-threonate normalized the neuroinflammation, synaptic potentiation and Mg2+ deficiency, but did not affect the estrogen decline in ovariectomized and aged mice. Furthermore, in cultured dorsal root ganglion neurons, estrogen at physiological concentration elevated intracellular Mg2+, and downregulated phospho-p65, tumor necrosis factor-alpha and interleukin-1 beta exclusively in the presence of extracellular Mg2+.Conclusion: Estrogen decline in menopause may cause neuroinflammation by reducing intracellular Mg2+ in neurons, leading to chronic pain, memory/emotional deficits. Supplement Mg2+ by oral magnesium-L-threonate may be a novel approach for treating menopause-related neuronal disorders.Keywords: magnesium-L-threonate, postmenopause, neuroinflammation, chronic pain, memory, depression